Optimización de costos en extracion de mineral, implementando chimenea raise boring como ore pass del nivel 1915 al nivel 1467 de la mina Papagayo- Poderosa - Mallqui Carranza, Edgar Anthony (2019)
In Cía. Minera Poderosa, this project is carried out in order to reduce the costs of extracting ore from the Rósamela and Rosaura veins, before the project is extracted on rails at levels 1915, 1800, 1600 and 1467 with electric locomotives and G-cars 60 and G-140 and Tunnel Virus The ore is transported in dumps to Marañón silver; which results in the increase of the unit costs of extraction ($ 19.9 / MT). Taking as reference this main problem, a study was made to implement a new extraction route to reduce the cost of mineral extraction, by building a Raise Boring Chimneys from level 1915 to level 1467 as Ore Pass, which will be built in a strategic zone in order to reduce the distance of travel of extraction equipment. For the study information was collected from various bibliographic sources which provide us with additional information to be able to structure our research, this information can be contrasted with the results obtained in the study of the project, which were collected and analyzed to be able to endorse or refute our hypothesis. A technical study was carried out, as well as time control, performance before and after the execution of the project, as well as an economic study to verify if the project from the financial point of view is profitable.